SMALL STEPS, BIG IMPACT: CO-CREATING CUSTOMER EXPERIENCE AND ONLINE PRESENCE IN A TRADITIONAL SRI LANKAN RESTAURANT - Jayasinghe, J.M.T.D.N.; Dilogini, S. (My University, 2025)
This Participatory Action Research (PAR) article explores how simple steps and actions can lead to a positive customer experience, operational efficiency, and online visibility at Inpa Pillaiyar Veg Restaurant, a traditional style restaurant in Kondavil, Sri Lanka. The PAR methodology involved planning (identifying customer concern points), acting (installing unwrapped food display shelves, switching to glass cups, introducing digital tools), observing (monitoring sales and feedback), and reflecting (revising staff training). Over two PAR cycles spanning six months, student-researcher and restaurant staff worked together to define customer concern points, implement interventions, and reflect on their actions. Physical interventions included installing unwrapped food display shelves, replacing metal tea cups with glass, improving lighting in the restaurant, and changing printed menus to make the dining environment more welcoming. Digital changes included mapping the restaurant on Google Maps, creating a new Facebook presence, and basic digital accounting to increase discovery and organization. These low-cost innovation, co-created improvements increased customer experience, online presence, and improved employee engagement. Physical improvements were combined with digital improvements to ensure participation and sustainable change. Therefore, the unique contribution of this study is the combination of tangible in-store improvements with accessible digital visibility, creating a dual-focus model that preserves heritage. While undergraduate marketing students often learn theories in lecture halls, this PAR project allowed students to apply marketing concepts in real-world settings and create actionable change. It also highlights how participatory approaches allow owner and employees to own changes, ensuring that interventions, no matter how small, are contextual and sustainable. These results offer potential value for similar small food businesses in low-income communities in Sri Lanka and beyond.
Keywords: Apply Marketing Concepts; Customer Experience; Digital Integration; Low-Cost Innovation; Online Presence; Participatory Action Research